Program Bina Desa Berbasis Akuafarming Dalam Program Piknik (Pendidikan Akuaponik) Di Pulau Panjang, Lepar Pongok, Bangka Selatan - ardiansyah kurniawan; Olivia Khanati; Eka Nurcahyono; Febi Kurniawati; Kiki Arizona; Sandika Wahyudi; Rina Apriyanti; Mustobi Prananda; Heru Anggara (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Panjang Island is one of the islands in the Lepar Pongok District, South Bangka Regency, Province of Bangka Belitung Islands. The inhabitants of this island rely on marine resources for their livelihood as fishermen. The catch often results in non-economic fish which becomes wasted. The island also has limited vegetable resources. Program of village development implements aquaponics education to provide initial knowledge about fish and vegetable cultivation by utilizing fish waste as fish feed. Aquaponic education uses a demonstration plot method that involves the community in the process. After the aquaponics construction was completed, an explanation of the system and its management was given to the community. Panjang Island residents are enthusiastic to know more details and also learn about aquaponics.